Household decisions, gender, and development: A synthesis of recent research - Quisumbing, Agnes R.; Ramakrishnan, Usha; Regmi, Shibesh; Ruel, Marie T.; Scrimshaw, Nevin; Sharma, Manohar; Skoufias, Emmanuel; Smith, Lisa C.; Cooke St. Clair, Priscilla; Thomas, Duncan; Udry, Christopher R.; Zwarteveen, Margaret (International Food Policy Research Institute, 2003)
This book synthesizes IFPRI's recent work on the role of gender in household decisionmaking in developing countries, provides evidence on how reducing gender gaps can contribute to improved food security, health, and nutrition in developing countries, and gives examples of interventions that actually work to reduce gender disparities. It is an accessible, easy-to-read synthesis of the gender research that IFPRI has undertaken in the 1990s.